Metabolomics analysis for quorum sensing biomarkers in Pseudomonas aeruginosa biofilms - Chen, Junzheng (2014)
Pseudomonas aeruginosa is an opportunistic pathogen that causes a wide range of medical problems and can be difficult to eradicate by conventional antimicrobials due to formation of biofilms. Quorum sensing, the process by which bacteria communicate with each other through the use of chemical signals, plays a pivotal role in biofilm formation. Through a metabolomics approach, we aim to study the metabolic processes of wild-type P. aeruginosa PAO1 strain and its relationship to biofilm formation, and also discover biomarkers which could be used for biofilm detection. From our chemostat setup, the expression of QS signals from rhlA, lasB and pqs reporter genes were reportedly the highest at 0.03 dilution rate. A comparison between NMR spectra shows that rhamnolipid and 2-heptyl-4-quinolone were found to be higher in a nutrient limited environment (ABTG media). By matching the NMR peaks with online databases (MMCD and KEGG), we have identified potential biomarkers related to Pseudomonas Quinolone Signal mediated quorum sensing and isoleucine synthesis pathway. Using LCMS analysis as a complement, D-erythro-3-Methylmalate was identified as a precursor of isoleucine. This demonstrates metabolomics is a flexible and systemic approach towards understanding metabolic network of quorum sensing mechanism and discovery of biomarkers.